Analysis of Information Technology Maturity Level For Academic Services Using Cobit 2019 Framework: Case Study of Global University Jakarta - Ary Wibowo; Antonius Darma Setiawan; Sinka Wilyanti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The use of information technology (IT) in managing academic services at universities is a strategic step to improve service efficiency and quality. Universitas Global Jakarta has implemented an academic information system, but still encounters obstacles in terms of information accuracy and control, indicating the need for an evaluation of the implemented IT governance. This study aims to assess the maturity level of IT governance in Universitas Global Jakarta's academic services using the COBIT 2019 framework, specifically the Delivery, Service, and Support (DSS) domain. The research method used is a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation studies. The results show that several processes in the DSS domain have not reached an optimal level of maturity, especially in the aspects of operational supervision and control. This finding indicates the need for improvements in the implementation of IT governance to be more aligned with the university's strategic objectives and able to support academic services sustainably.